The psychological perspective on the adoption of approved genetically modified crops in the presence of acceptability constraint: the contingent role of passion. Issue 4 (2nd October 2019) - Ali, Sumran; Ghufran, Muhammad; Nawaz, Muhammad Asim; Hussain, Sumaira Nazar
ABSTRACT: This study contributes to the literature on genetically modified crops by examining the impact of psychological distance on farmer adoption. The existing body of literature suggests that some farmers have the conservative perception to adopt genetically modified crops because of controversies regarding the side effects and profitability. To understand these social problems, we have relied upon construal-level theory which argues farmer passion about dynamics like here and now, likely or unlikely and the near or far from self are vital for the adoption of approved genetically modified crops. The data for the present study collected from three Asian countries through questionnaire, for China 300, India 350, Philippines 300 valid responses collected. The study founds a positive relation of psychological distance based on passion with farmer trust behavior to adopt genetically modified crops over time. The findings of the present study provide new insights into the development of farmer acceptability and encourage the use of novel crop technologies. Abbreviations: GM, genetically modified; TD, temporal distance; SPD, Spatial distance; SD, Social distance; TB, trust behavior; AGMC, Approved Genetically modified crops; CLT, Construal Level Theory